(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The furniture is of primary importance towards the canopies definition, more than the architectonic structure: they contribute, in fact, in creating and organizing the spaces, so that there is almost no distinction between furniture and structure, as it is possible to observe in the ancient sources of different periods (Herodotus, Euripides, Julius Caesar, Plutarchus, Athenaeus): the pavilions of Xerxes at Plataia, of Ion at Delphi, of Alexander after the Issa battle and at Susa, of Pompey at Pharsalos, as well as the Ptolomaeus’s canopy at Alexandria. At the same time, the furniture language is studied, signifying the power and the force of the sovereign through the luxurious materials and surprising the spectators. At the end, some hypotheses on the final destination of the furniture, after dismantling the Ptolomaeus’ canopy, equiped for one year.